2016
DOI: 10.5194/hess-2016-216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Relationship between Teleconnections and Taiwan's Streamflow: Evidence of Climate Regime Shift and Implications for Seasonal Forecasting

Abstract: Abstract. Interannual variations of catchment streamflow represent an integrated response to anomalies in regional moisture transport and atmospheric circulations, ultimately linked to large-scale climate oscillations. This study investigates the relationship between Taiwan's long-term summertime (July to September, JAS) streamflow and manifold teleconnection patterns. Discussion about the changes in pattern correlation and composite maps before and after the change point is carried out, and our results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…When comparing the results of the previous studies that analyzed correlations between precipitation in the Korean Peninsula and global climate indices with the results presented in Figure 8, common results were found for some indices although the areas and periods were different. Cho et al [9] used the indices of AO (5) in February, AO (8) in May, and NAO (6) in June for predicting monthly precipitation in the Andong Dam basin. Kim and Kim [24] analyzed correlations between the global climate indices and the monthly precipitation of 60 weather stations in South Korea and found that the indices of AO (5) and NAO (6) were highly correlated with the precipitation in February and June, respectively.…”
Section: Application Frequency Of Climate Indicesmentioning
confidence: 99%
“…When comparing the results of the previous studies that analyzed correlations between precipitation in the Korean Peninsula and global climate indices with the results presented in Figure 8, common results were found for some indices although the areas and periods were different. Cho et al [9] used the indices of AO (5) in February, AO (8) in May, and NAO (6) in June for predicting monthly precipitation in the Andong Dam basin. Kim and Kim [24] analyzed correlations between the global climate indices and the monthly precipitation of 60 weather stations in South Korea and found that the indices of AO (5) and NAO (6) were highly correlated with the precipitation in February and June, respectively.…”
Section: Application Frequency Of Climate Indicesmentioning
confidence: 99%